2020
DOI: 10.1542/peds.2019-0377
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Effectiveness of the PCV-10 and PCV-13 Vaccines Against Invasive Pneumococcal Disease

Abstract: CONTEXT: Pneumococcal conjugate vaccines (PCVs) (pneumococcal 13-valent conjugate vaccine [PCV-13] and pneumococcal 10-valent conjugate vaccine [PCV-10]) are available for prevention of pneumococcal infections in children. OBJECTIVE: To determine the vaccine effectiveness (VE) of PCV-13 and PCV-10 in preventing invasive pneumococcal disease (IPD) and acute otitis media (AOM) in children ,5 years. DATA SOURCES: Systematic searches of Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 37 publications
(81 reference statements)
1
24
0
3
Order By: Relevance
“…1 ). Although some variations in vaccine effectiveness have been reported by each study, multiple studies have reported the effectiveness of the 3 primary doses plus a booster dose (3 + 1) schedule as being approximately 85%–86% for the primary doses and 90%–91% for the booster dose [ [46] , [47] , [48] , [49] ]. In our model, the vaccine effectiveness of PCV13 for the prevention of VT IPD was assumed to be 86.0% for the primary doses and 90.3% for the booster dose [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Although some variations in vaccine effectiveness have been reported by each study, multiple studies have reported the effectiveness of the 3 primary doses plus a booster dose (3 + 1) schedule as being approximately 85%–86% for the primary doses and 90%–91% for the booster dose [ [46] , [47] , [48] , [49] ]. In our model, the vaccine effectiveness of PCV13 for the prevention of VT IPD was assumed to be 86.0% for the primary doses and 90.3% for the booster dose [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our model, the vaccine effectiveness of PCV13 for the prevention of VT IPD was assumed to be 86.0% for the primary doses and 90.3% for the booster dose [ 47 ]. This variation was explored in our sensitivity analysis using a vaccine effectiveness range of 75%–99% [ [46] , [47] , [48] , [49] , [50] ]. The vaccine effectiveness for colonization was assumed to be 53% in our model [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immunization strategies that seek to enhance opsonophagocytic killing of pathogens have been most successful with microbes encoding a prominent capsule. Thus, childhood vaccines that target H. influenzae and S. pneumoniae capsule have dramatically reduced invasive diseases caused by these major pathogens [ 74 , 75 ]. S. aureus , in comparison, makes a small capsule and relies on a broader array of virulence factors to establish infection in different tissues.…”
Section: Immune Boosting Strategiesmentioning
confidence: 99%
“…Young children are considered the most important vector for the dissemination of pneumococci within the community because of their high frequency of nasopharyngeal carriage [3]. Pneumococcal conjugated vaccines (PCVs) were licensed in 2000 and their use has a substantial impact on the burden of pneumococcal disease leading to a significant reduction in invasive pneumococcal disease through direct and indirect protection [4][5][6]. Different amounts of pneumococcal antibodies are required to protect against systemic disease and colonization, with higher titers needed for protection against certain serotypes and mucosal colonization [7][8][9].…”
Section: Introductionmentioning
confidence: 99%